Runners injuries - main types of injuries of the musculoskeletal system of the lower limb and their treatment and prevention - Marta Głąbień; Paweł Miłkowski; Aleksandra Rajewska; Joanna Długosz; Jędrzej Rajewski; Agnieszka Jolanta Łoś; Justyna Drużyńska; Dagmara Ragan; Maciej Bara; Paweł Staszczak (Nicolaus Copernicus University in Toruń, 2024)
Introduction and purpose Running is currently one of the most popular physical activities practiced by people around the world, and the number of runners has been growing significantly for many years. The incidence of running-related lower limb injuries in runners ranges between 19.4% and 79.3% [1]. The paper presents research results on the main types of injuries of the musculoskeletal system of the lower limb in runners, their risk factors, methods of treatment and prevention. The results indicate a significant relationship between regular training and the occurrence of injuries, and also emphasize the importance of prevention through rest, appropriate running technique and the selection of footwear. The work provides practical tips for runners and coaches that can help reduce the risk of injuries and improve the quality of training. Materials and methods The review was conducted by searching PubMed and other scientific databases focusing on currently available publications. The literature available in the PubMed database was reviewed using the following keywords: "running", "running injuries", "tendinopathy", "running related injuries", "running biomechanics", "musculoskeletal injuries". The analysis of  38 articles published between 2014-2024 was used to write the paper. Conclusions Running has many health benefits, but unfortunately it can also have a negative effect. The development of medical literature regarding appropriate prevention, knowledge of risk factors and treatment methods improves the prognosis of injuries in runners. Evolving diagnostic imaging, body monitoring, prevention, and adequate rest between activities are essential to long-term success in preventing running-related injuries.